FAKTOR-FAKTOR YANG MEMPENGARUHI IBU MENYUSUI DALAM MASA PANDEMI COVID-19: LITERATUR REVIEW - Merida Simanjuntak (AKPER Pasar Rebo, 2021)
Background: The COVID-19 pandemic is impacting lives in many aspects. Various ways are done to reduce the spread of the virus that has an impact on the post-partum adaptation period especially in breastfeeding. This study aims to review the factors that affect mothers in breastfeeding during the COVID-19 pandemic. Method: Literature Review is conducted referring to the issue, methodology and equation of the results obtained as well as the methods used. There are 6 articles used in the literature review. Data searches are conducted in international and national journals. The results showed similarities in support factors from health workers and were influenced by the policies imposed. Need to improve support from the family, availability of health information, policies and applications of communication technology as a supporting factor in breastfeeding and improve maternal and infant health.